A Rare Case of a Right Atrial Paraganglioma in an Individual with the SHDB Mutation - Ian Lancaster; Carlos Nunez; Andrew Willinger; Christiano Caldeira; Jeffrey Aufman (Case Reports in Cardiology)
Paragangliomas are extra-adrenal chromaffin cell tumors. A small percentage of these tumors can be found in the thoracic cavity and, when in the heart, are typically in the left atrium. In this case report, we discuss the case of an individual with a history of several paragangliomas with the SHDB mutation who was found to have two cardiac paragangliomas in the right atrium.